Involvement in Self employment among Returnee Migrants in Chitwan - Tiwari, Pradip Raj (BMC Journal of Scientific Research, 2018)
Motivated by emerging issues of migration in Nepal, particular to returnee migrants, this paper examines the situation of returnee migrants and their participation in self employment based on cross-sectional data from 243 returnee migrants in three VDCs of Chitwan. The result shows that age, education, country of returned and re-migration plan are the major determinants of participation in self employment among returnee migrants where adult returnee migrants were more likely to engage in self employed compare to youth. The result also shows that the Gulf and Malaysian returnees who are not eager to migration again are more likely (odd ratio=2.645, p